Egg : a culinary exploration of the world's most versatile ingredient - Ruhlman, Michael, 1963-; Ruhlman, Donna Turner (New York : Little Brown & Co, 2014)
Offers over one hundred recipes for dishes featuring eggs, from simple techniques for making poached and scrambled eggs, to reci
Introduction -- Egg/whole/cooked in shell -- Egg/whole/cooked out of shell -- Egg/whole/cooked out of shell/blended -- Egg/as ingredient/the dough-batter continuum -- Egg/separated/the yolk -- Egg/separated/the white -- Egg/separated but used together.
Includes index.
Includes removable illustrated flowchart.
Keywords: Cooking (Eggs); Eggs; Cooking (Eggs); Eggs; Cooking (Eggs); Eggs; Cookbooks; Cookbooks; Cookery